Eruptive mass loss less than a year before the explosion of superluminous supernovae: I. The cases of SN 2020xga and SN 2022xgc - Gkini, A.; Fransson, C.; Lunnan, R.; Schulze, S.; Poidevin, F.; Sarin, N.; Koenyves-Toth, R.; Sollerman, J.; Omand, C. M. B.; Brennan, S. J.; Hinds, K. R.; Anderson, J. P.; et al. (EDP Sciences, 2025)
We present photometric and spectroscopic observations of SN 2020xga and SN 2022xgc, two hydrogen-poor superluminous supernovae (SLSNe-I) at z = 0.4296 and z = 0.3103, respectively, which show an additional set of broad Mg II absorption lines, blueshifted by a few thousands kilometer second(-1) with respect to the host galaxy absorption system. Previous work interpreted this as due to resonance line scattering of the SLSN continuum by rapidly expanding circumstellar material (CSM) expelled shortly before the explosion. The peak rest-frame g-band magnitude of SN 2020xga is -22.30 +/- 0.04 mag and of SN 2022xgc is -21.97 +/- 0.05 mag, placing them among the brightest SLSNe-I. We used high-quality spectra from ultraviolet to near-infrared wavelengths to model the Mg II line profiles and infer the properties of the CSM shells. We find that the CSM shell of SN 2020xga resides at similar to 1.3 x 10(16) cm, moving with a maximum velocity of 4275 km s(-1), and the shell of SN 2022xgc is located at similar to 0.8 x 10(16) cm, reaching up to 4400 km s(-1). These shells were expelled similar to 11 and similar to 5 months before the explosions of SN 2020xga and SN 2022xgc, respectively, possibly as a result of luminous-blue-variable-like eruptions or pulsational pair instability (PPI) mass loss. We also analyzed optical photometric data and modeled the light curves, considering powering from the magnetar spin-down mechanism. The results support very energetic magnetars, approaching the mass-shedding limit, powering these SNe with ejecta masses of similar to 7 - 9 M-circle dot. The ejecta masses inferred from the magnetar modeling are not consistent with the PPI scenario pointing toward stars > 50 M-circle dot He-core; hence, alternative scenarios such as fallback accretion and CSM interaction are discussed. Modeling the spectral energy distribution of the host galaxy of SN 2020xga reveals a host mass of 10(7.8) M-circle dot, a star formation rate of 0.96(-0.26)(+0.47) M-circle dot yr(-1), and a metallicity of similar to 0.2 Z(circle dot).